2013
DOI: 10.1371/journal.pgen.1003365
|View full text |Cite
|
Sign up to set email alerts
|

Rare Copy Number Variants Are a Common Cause of Short Stature

Abstract: Human growth has an estimated heritability of about 80%–90%. Nevertheless, the underlying cause of shortness of stature remains unknown in the majority of individuals. Genome-wide association studies (GWAS) showed that both common single nucleotide polymorphisms and copy number variants (CNVs) contribute to height variation under a polygenic model, although explaining only a small fraction of overall genetic variability in the general population. Under the hypothesis that severe forms of growth retardation mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 37 publications
(36 reference statements)
2
53
0
4
Order By: Relevance
“…Our results draw attention to the fact that pathogenic and probably pathogenic variants detected occurred in different chromosomal regions, which could explain the clinical variability of the SGA patients investigated in the present study. The same genetic variability was observed in the pathogenic and probably pathogenic CNVs in the two studies mentioned above (12,13). CNVs categorized as pathogenic or probably pathogenic in the present study fulfill some established deleterious criteria.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results draw attention to the fact that pathogenic and probably pathogenic variants detected occurred in different chromosomal regions, which could explain the clinical variability of the SGA patients investigated in the present study. The same genetic variability was observed in the pathogenic and probably pathogenic CNVs in the two studies mentioned above (12,13). CNVs categorized as pathogenic or probably pathogenic in the present study fulfill some established deleterious criteria.…”
Section: Discussionsupporting
confidence: 84%
“…In a recent study, underlying pathogenic CNVs have been identified in 20 of 200 patients (10%) with short stature without an apparent cause; eight of these 20 patients were born SGA (13). In another study, genome-wide analysis of CNVs of 162 patients with short stature of unknown origin revealed at least 17 (10.4%) pathogenic variants, regarding familial segregation (12).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Four recent studies (153,215,216,217) showed that w10% of patients with ISS carry a disease-causing CNV, and in short children microdeletions (in contrast to microduplications) are significantly more frequent than in controls (218). However, for individual cases one often remains uncertain whether their growth failure is due to the encountered CNV, and which of the genes is responsible for it.…”
Section: Copy Number Variantsmentioning
confidence: 99%
“…Second, as the authors correctly note, a routine exome analysis does not detect genomic deletions or duplications or methylation abnormalities. Numerous groups have shown that genomic copy number variants (deletions and duplications) underlie a significant portion of patients with severe growth disorders [6,7], and the article by Storr et al [4] suggests that SilverRussell syndrome may be a cause for a number of these patient's short stature. Silver-Russell syndrome is most commonly caused by methylation abnormalities which will not be identified by exome sequencing.…”
Section: Doi: 101159/000481285mentioning
confidence: 99%